2016
DOI: 10.1152/ajpendo.00356.2015
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β inhibits β-Klotho expression and FGF19 signaling in hepatocytes

Abstract: Fibroblast growth factor (FGF) 19 is a member of the FGF15/19 subfamily of FGFs that includes FGF15/19, FGF21, and FGF23. FGF19 has been shown to have profound effects on liver metabolism and regeneration. FGF19 binds to FGFR4 and its coreceptor β-Klotho to activate intracellular kinases, including Erk1/2. Studies have shown that proinflammatory cytokines such as TNFα impair FGF21 signaling in adipose cells by repressing β-Klotho expression. However, little is known about the effects of inflammation on the FGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 45 publications
(65 reference statements)
1
39
0
Order By: Relevance
“…Fgf15 also has the ability to directly suppress inflammation via signaling through its receptor Fgfr4 (47). Given that hepatocytes are the only cell type in liver that expresses the Fgf15 receptor complex Fgfr4-␤Kl, it is logical to speculate that increased Fgf15 in ethanol-fed mNTKO mice might exert anti-inflammatory effects by targeting hepatocytes (49).…”
Section: Discussionmentioning
confidence: 99%
“…Fgf15 also has the ability to directly suppress inflammation via signaling through its receptor Fgfr4 (47). Given that hepatocytes are the only cell type in liver that expresses the Fgf15 receptor complex Fgfr4-␤Kl, it is logical to speculate that increased Fgf15 in ethanol-fed mNTKO mice might exert anti-inflammatory effects by targeting hepatocytes (49).…”
Section: Discussionmentioning
confidence: 99%
“…circadian regulator, are important repressors of β-klotho gene expression [64,103,104]. There is compelling evidence indicating that the liver coordinates global metabolism, both at rest and in times of stress, through multiorgan crosstalk by secreting FGF21 as well as some other hepatokines [105].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…There are observations indicating that the expression of β-klotho is reduced in metabolic diseases which impairs signaling through the FGFR1/β-klotho complex [76,174]. Chronic inflammation, a phenomenon associated with metabolic and stress-related disorders, is a potent inhibitor of β-klotho expression [64,104]. The crucial role of β-klotho deficiency in FGF21 resistance was highlighted in an experiment which revealed that the overexpression of β-klotho increased the sensitivity of mouse adipose tissue to…”
Section: Fgf21 Resistance Disturbs the Healthy Aging Processmentioning
confidence: 99%
“…Thus, the hepatic inflammation observed in Klb -/-mice may result directly from the lack of FGF21 signaling. Several reports have recently described a feedback loop between FGF21 signaling and inflammation; inflammatory mediators decrease FGF21 signaling through Klb-specific repression (54,55), and in turn, FGF21 signaling exerts antiinflammatory effects (56)(57)(58). Interestingly, in the nonobese model of fatty liver disease, FGF21 deficiency also worsened ER stress and inflammation (59,60).…”
Section: Tgr5mentioning
confidence: 99%